Blocking The Poor And The Huddled Masses : The Shift in the United States Immigration Policy during Trump’s Presidency - Abdelatif Imene, Hamre laine Fatima (My University, 2019)
V ABSTRACT This dissertation deals with President Donald Trump‘s Major executive orders toward legal and illegal immigrants, as well as highlighting the effect of those orders on immigrants. This study mainly focuses on the modification of American immigration‘s system that Trump had promised with radical changes. Immigration has been an issue which has taken U.S political debates; President Trump was elected to take extraordinary actions to restrict immigrants flow to the immigrants to the country, including building a wall barrier across the southern border , deporting million of undocumented immigrants and blocking the coming of certain minorities from coming the U.S. Moreover, after his inauguration, Trump had executed orders which mainly were, blocking immigrants from seven countries with Muslim majority from entering to the U.S, signing executive order calling for the complete construction to the wall between Mexico and the U.S and obliging Mexico to bay for it. Moreover, in order to restrict the coming of legal immigrants to the U.S he introduced new rules for the public charge, whereas he cancelled Differed Action Childhood Arrivals ( DACA) program in order cut down the aiding program that most undocumented immigrants depend on it , and announcing lass deportation operation for the undocumented immigrants . Those actions were having a harm effect on immigrants whether legal or not; many immigrants suffered on the airport due to the ban, whether others were obliged to deport to their countries due to the large deportation operation whether were facing the split of their families with the coming executive orders, but the immigrants or administrations officers were opposing trump through different means like aiding those targeted immigrants and protecting them from the federal government orders. No administration in the world had focused on immigration rather than the administration of Donald Trump aiming to restrict the flows of immigrants and deporting the undocumented ones.
Keywords: Immigration system, aliens, refugee, undocumented immigrants, exclusion.